2022
DOI: 10.3389/fnhum.2021.771392
|View full text |Cite
|
Sign up to set email alerts
|

Indices of Loading and Propulsive Ability in the Gait of Patients With Chronic Stroke With Equinus Foot Deviation: A Correlation Study

Abstract: In literature, indices of overall walking ability that are based on ground reaction forces have been proposed because of their ease of administration with patients. In this study, we analyzed the correlation between the indices of dynamic loading and propulsion ability of 40 chronic hemiparetic post-stroke patients with equinus foot deviation and a set of clinical assessments of ankle joint deviations and walking ability. Ankle passive and active range of motion (ROM) and triceps surae spasticity were consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In the literature, TUG and BERG tests [14,[24][25][26] for balance assessment in hemiplegia patients, MAS scoring [27] for spasticity assessment, MMSE [28] for mental status, and RMI [29] for functional status are frequently used. To determine the efficacy of the treatments, the parameters were evaluated with pre-test and posttests.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, TUG and BERG tests [14,[24][25][26] for balance assessment in hemiplegia patients, MAS scoring [27] for spasticity assessment, MMSE [28] for mental status, and RMI [29] for functional status are frequently used. To determine the efficacy of the treatments, the parameters were evaluated with pre-test and posttests.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study by Mazzoli et al ( 54 ) showed a good correlation between indices based on ground reaction force and clinical and functional variables. Since the acquisition of ground reaction forces does not require patient preparation, it can be used in clinical routine and especially for postoperative evaluation ( 79 ). An alternative is to use combined accelerometric and gyroscopic data on an inertial measurement unit (IMU).…”
Section: Discussionmentioning
confidence: 99%